2016
DOI: 10.1016/j.cherd.2016.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of oblique impact of particles on wet surfaces

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Greater magnitude of oblique rebound angles during collisions are most likely to be the result of morphology influence in terms of particle shape rather than roughness (i.e., meso-scale morphology expressed by particle shape is more crucial compared with micro-to-nano scale morphology expressed with roughness to cause no vertical rebound of the grains). However, oblique rebound angles can also be observed if the experiments were conducted at an impact angle (for example: Sommerfeld and Huber [47], Cruger et al [48], Tang et al [24]).…”
Section: Effect Of Surface Roughness On Cormentioning
confidence: 99%
“…Greater magnitude of oblique rebound angles during collisions are most likely to be the result of morphology influence in terms of particle shape rather than roughness (i.e., meso-scale morphology expressed by particle shape is more crucial compared with micro-to-nano scale morphology expressed with roughness to cause no vertical rebound of the grains). However, oblique rebound angles can also be observed if the experiments were conducted at an impact angle (for example: Sommerfeld and Huber [47], Cruger et al [48], Tang et al [24]).…”
Section: Effect Of Surface Roughness On Cormentioning
confidence: 99%
“…For experimental validation mainly results of our previous works (Crüger et al, 2016a;Crüger et al, 2016b;Buck et al, 2017) were used. Additionally, some new experiments were conducted.…”
Section: Experimental Validationmentioning
confidence: 99%
“…in normal direction by Barnocky and Davis (1988), Hogekamp et al (1994), Davis et al (2002), Kantak et al (2005), Antonyuk et al (2009), Sutkar et al (2015), Gollwitzer et al (2012), Fu et al (2004) as well as in Crüger et al (2016a). Wet oblique collision experiments with thin liquid layers were exemplary conducted by Kantak and Davis (2004), Ma et al (2013Ma et al ( , 2015Ma et al ( , 2016, Crüger et al (2016b), Buck et al (2017). In comparison to collisions immersed in liquid, in the case of thin layers the layer thickness has additionally to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the importance of liquid layer thickness, it was found that the e wet in the normal direction decreases significantly with increasing layer thickness . Conversely, increasing layer thickness has no further effect on the e wet in the tangential direction rather than causing less friction . With respect to the influence of impact velocity, the wet restitution coefficient was found to increase with the impact velocity (beyond a critical value) before leveling out to reach a plateau .…”
Section: Introductionmentioning
confidence: 94%